Recent Progress of Layered Perovskite Solar Cells Incorporating Aromatic Spacers - Gao, Yuping; Dong, Xiyue; Liu, Yongsheng (Nano-Micro Letters, 2023)
Layered two dimensional (2D) or quasi-2D perovskites are emerging photovoltaic materials due to their superior environment and structure stability in comparison with their 3D counterparts. The typical 2D perovskites can be obtained by cutting 3D perovskites along < 100 > orientation by incorporation of bulky organic spacers, which play a key role in the performance of 2D perovskite solar cells (PSCs). Compared with aliphatic spacers, aromatic spacers with high dielectric constant have the potential to decrease the dielectric and quantum confinement effect of 2D perovskites, promote efficient charge transport and reduce the exciton binding energy, all of which are beneficial for the photovoltaic performance of 2D PSCs. In this review, we aim to provide useful guidelines for the design of aromatic spacers for 2D perovskites. We systematically reviewed the recent progress of aromatic spacers used in 2D PSCs. Finally, we propose the possible design strategies for aromatic spacers that may lead to more efficient and stable 2D PSCs. Highlights: 1 Layered two-dimensional (2D) perovskites are emerging photovoltaic materials with superior structural and environmental stability. 2 Aromatic spacers offer unique advantages over aliphatic spacers, including higher dielectric constants, better charge transport properties, and the ability to regulate crystal arrangement, making them indispensable for constructing efficient and stable 2D perovskites. 3 This review mainly focus on recent progress and achievements in developing aromatic spacer-based 2D perovskite solar cells.